Effective use of social media opportunities in the education and training of generation Z - Бейсенбаева, Айгуль; Жұмаадан, Айсұлу (Pedagogy and Psychology, 2022)
The article is devoted to determining the role of digital technologies and social networks in the pedagogical process and considering ways to update modern methods of upbringing and teaching a child. A comparative characteristic of representatives of generation Z is given. The possibilities and advantages and disadvantages of the social network "Tik Tok" are shown, which allows organizing the educational process taking into account the specific features of generation Z. A questionnaire has been compiled for elementary school students, parents and teachers.The results of the survey are analyzed, ways of effectively using the capabilities of the "Tik Tok" network in the educational process are proposed, and an analytical table on the advantages and disadvantages of digital devices and social networks is compiled. A reference is given to literature useful to parents in raising children of generation Z. The authors attempted to draw meaningful conclusions about digital competencies and information culture.